Defining digital coaching: a qualitative inductive approach - Diller, Sandra J.; Passmore, Jonathan (Frontiers in Psychology, 2023)
The term 'digital coaching' is widely used but ill-defined. The present study therefore investigates how digital coaching is defined and how it differentiates from face-to-face coaching and other digital-technology-enabled (DT-enabled) formats, such as digital training, digital mentoring, or digital consulting. A qualitative inductive approach was chosen for more in-depth and open-minded content. Based on previous studies on the importance of asking coaches working in the field, 260 coaches working in the field of digital coaching were surveyed. The given answers depict the importance of differing between forms of DTenabled coaching. Thus, digital coaching is a DT-enabled, synchronous conversation between a human coach and a human coachee, which is different to artificial intelligence (AI) coaching and coaching that is supported by asynchronous digital and learning communication technologies. Due to this definition and differentiation, future studies can explore the digital coaching process and its effectiveness -particularly in comparison to other formats. Furthermore, this clear definition enables practitioners to maintain professional standards and manage client's expectations of digital coaching.while helping clients understand what to expect from digital coaching.